When disaster strikes: The role of disaster planning and management in cancer care delivery. Issue 15 (18th May 2020) - Sahar, Liora; Nogueira, Leticia M.; Ashkenazi, Isaac; Jemal, Ahmedin; Yabroff, K. Robin; Lichtenfeld, J. Leonard
Abstract : The impact of disasters on the delivery of health services suggests that patients with cancer should be identified as a vulnerable population that requires additional attention and assistance during a disaster. Incorporating the special case of these patients into an event management framework can elevate resilience, decrease suffering, and save lives.